Contribution to Analysis and Evaluation the Chemical, Physical Properties of Construction &Demolition Wastes & Aggregates - ناجي ديوب; هيثم شاهين; عماد فاضل (Latakia University Journal -Engineering Sciences Series, 2024)
Construction &Demolition Wastes are widely recognized as the main waste stream around the word, and their recycling and recovery is a main issue in many studies and researches of Organizations and Academic centres. In spite of good performance of recycled C&D in general, it is still outspread in our Country. The composition of Construction &Demolition Wastes is highly heterogeneous and is influenced by several factors, including the raw materials and construction product used. The performance of these materials is considerably variable, and in some cases don’t comply with the environmental regulations. C&D waste recycling is considered as important issue, especially in the regions of natural disasters and conflicts, which usually lead to huge amounts of C&D wastes. The research aims to study and evaluate the Chemical, Physical Properties of Construction &Demolition Wastes & Aggregates, to determine their reusing aspects.